CuCo and sulfur doped carbon nitride composite as an effective Fenton-like catalyst in a wide pH range - Lin, Feifei; Liu, Peng; Lin, Rundong; Lu, Chen; Shen, Yuanyuan; Wang, Yongqiang; Su, Xiwen; Li, Hongjiang; Gu, Ying-Ying (Frontiers in Chemistry, 2022)
The heterogeneous Fenton-like reaction, as an advanced oxidation process, is widely recognized attributed to its recyclability, wide pH response range, easy solid-liquid separation, and non-production of iron sludge. Recently, the bimetallic catalysts have attracted intense attention due to their high catalytic performance and excellent stability over a wide pH range. In this article, CuCo/SCN bimetallic catalyst was prepared by pyrolysis method with sulfur doped carbon nitride (SCN) as the carrier. Under the conditions of pH=7, catalyst dosage of 0.8 g/L, and concentration of H2O2 of 15 mM, 20 mg/L of methyl orange (MO) can be completely removed within 1 h. With the synergistic action between bimetals and sulfur doped carbon nitride, the CuCO/SCN involved Fenton-like system exhibited excellent catalytic degradation efficiency and strong stability for MO in neutral and weak alkaline conditions. The EPR characterization proved that ·OH and ·O2- were the main active components. Furthermore, CuCo/SCN involved Fenton-like system has good adaptability. Bimetallic CuCo/SCN catalyst has great application potential in the degradation of environmental pollutants.